POLITIK NEGOSISASI DISKURSUS REKONSOLIASI 1965 DAN IMAJI KEINDONESIAAN PASCA-ORDE BARU - Narwaya, St.Tri Guntur; HT, Faruk; Budiawan, Budiawan (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2018)
During the dynamics of Post New Order Regime, various efforts to initiate the idea of ‘1965 reconciliation’ have emerged. Steps to reconciliation have been smoothly running. Formally, TAP MPR Number 5 Year 2000 and Law Number 26 Year 2000 have noticeably stipulated the issue. Reconciliation is considered one alternative to resolve violation of past crimes. The stipulation of the Law Number 27 Year 2004 on Truth and Reconciliation Commission was expected to reflect a great step to succeed. Nevertheless, this step has been challenged, which led to the abolishment of the Law on Truth and Reconciliation Commission by Constitutional Court (MK). After its abolishment, various efforts have been done in order to renegotiate and to provide new tactics and initiatives. Some initiatives have met and achieved their intended objectives. Some find them as successful efforts, while some others either individuals or members of social and religious organizations, as well as government elites consider those reconciliation initiatives as critical threats to the state. Some negative responses are firmly connected to dominating narratives of phobia or anti-communism, which remain flourishing until nowadays. Some contestations and narrative articulations are frequently related to the discourses of anticommunism, which have in some cases hindered the reconciliation efforts. Indeed, there is a need to deeply deciphering the future narratives of the 1965 reconciliation, particularly in the post New Order development.